2010
DOI: 10.1016/s0973-0508(10)80024-3
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission computed tomography evaluation in patients with mild to moderate head injury

Abstract: Head injury is a major cause of disability and death in adults. The commonest pathological substrate in patients dying with blunt head injury is ischemic brain damage. Evaluation of cerebral perfusion is currently not a standard practice. We reviewed the medical records of 40 patients with Mild & Moderate Head Injury (GCS 9?14) who had 43 SPECT brain perfusion studies (Tc99m-ECD). They were evaluated in relation to GCS, NCCT (TCDB) grading, timing of scan and other factors. It was found that some degree of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have reported the changes in biochemical measures like resting metabolic expenditure, nitrogen excretion, blood glucose, homocysteine, magnesium, and serum albumin in patients of SHI. 13,15,[18][19][20][21][22][23] But no study has been done so far on anthropometric assessment in patients of SHI.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the changes in biochemical measures like resting metabolic expenditure, nitrogen excretion, blood glucose, homocysteine, magnesium, and serum albumin in patients of SHI. 13,15,[18][19][20][21][22][23] But no study has been done so far on anthropometric assessment in patients of SHI.…”
Section: Discussionmentioning
confidence: 99%